For the Love of Elu: Steven Cohen's gentle endocannibalism. (17th November 2018) - Sassen, Robyn
Abstract : Put Your Heart under Your Feet … and Walk! is a work by South African-born performance artist Steven Cohen. It was exhibited in Johannesburg in 2017 and showcased during Dance Umbrella, a Johannesburg-based contemporary dance festival, in 2018, before travelling to Europe. The work, which manifests in two video works, entitled fat and blood respectively as well as a live performed component, debuted in June of 2017 at the festival for contemporary dance in Montpellier, France. It confronts the loss Cohen suffered in July 2016 when his life partner, Elu, a dancer and choreographer, died suddenly after a six-week-long illness. Cohen and Elu collaborated and lived together for over 20 years, effectively redefining contemporary performance in South Africa. In blood and fat, Cohen is filmed performing at a South African abattoir. He dresses in a costume evocative of balletic traditions. The wings of an Atlas moth adorn his face. He dances among cattle waiting to be slaughtered. He dances beneath the shuddering body of an animal as its life blood seeps from it. Throughout his career, Cohen has been unafraid to challenge boundaries of properness and permissibility; and in this piece, he performs endo-cannibalism and publicly consumes the cremated remains of Elu, in an act of worship. Having written about Cohen since 1998, I believe that his work in its radicalism may be aligned – aesthetically and politically – with the contribution Antonin Artaud made to 20th century performance, in terms of its exploration of ritual and the substance of life. While Cohen's focus on the rawness of mourning and the transient substance of life is powerful, he dances into the body fluids of the slaughtered animal, becoming almost corpse-like himself in his sense of abjection.